High-performance poly(lactide) composites by construction of network-like shish-kebab crystals. Issue 75 (26th July 2016) - Shen, Tianfeng; Xu, Yunsheng; Ma, Piming; Wang, Likui; Dong, Weifu; Chen, Mingqing
Abstract : Novel high-performance PLA composites were prepared by solid-state uniaxial stretching with the OXA as needle-like nucleation templates leading to a unique network-like shish-kebab crystal structures with a tensile strength above 120 MPa. Abstract : Poly(lactide), PLA, suffers from brittleness and poor heat-resistance. Herein, a novel strategy to in situ fabricate high-performance PLA composites is reported for the first time, i.e., by solid-state uniaxial stretching in the presence of N 1, N 1′ -(ethane-1, 2-diyl)bis( N 2 -phenyloxalamide) (OXA) as needle-like nucleation templates. As a consequence, a tensile strength of >120 MPa, an elongation at break of >25% and a heat-resistant temperature of >150 °C of the PLA composites are simultaneously achieved. The superior performances are ascribed to unique interlocked network-like shish-kebab crystal structures that formed upon solid-state hot-stretching in the presence of OXA. This research may create a new type of sustainable engineered plastic.